Reprogramming patient-iPSC specific retinal organoids for deciphering epigenetic modifications of RNA methylation - Chien, Yueh; Yang, Yi-Ping; Lin, Tai-Chi; Chiou, Guang-Yuh; Yarmishyn, Aliaksandr A; Wang, Chia-Hao; Ching, Lo-Jei; Lin, Yi-Ying; Chen, Shih-Jen; Hwang, De-Kuang; Hsu, Chih-Chien (Journal of the Chinese Medical Association, 2024)
Induced pluripotent stem cell (iPSC) technology has emerged as a powerful tool for disease modeling, providing an innovative platform for investigating disease mechanisms. iPSC-derived organoids, including retinal organoids, offer patient-specific models that closely replicate in vivo cellular environments, making them ideal for studying retinal neurodegenerative diseases where retinal ganglion cells (RGCs) are impacted. N6-methyladenosine (m6A), a prevalent internal modification in eukaryotic mRNAs, plays a critical role in RNA metabolic processes such as splicing, stability, translation, and transport. Given the high energy demands of RGCs, mitochondrial dysfunction, which leads to impaired ATP production and increased ROS levels, is often central to the progression of retinal neurodegenerative disorders. However, the epigenetic mechanisms underlying m6A modification and their contributions to these conditions remain unclear.BACKGROUNDInduced pluripotent stem cell (iPSC) technology has emerged as a powerful tool for disease modeling, providing an innovative platform for investigating disease mechanisms. iPSC-derived organoids, including retinal organoids, offer patient-specific models that closely replicate in vivo cellular environments, making them ideal for studying retinal neurodegenerative diseases where retinal ganglion cells (RGCs) are impacted. N6-methyladenosine (m6A), a prevalent internal modification in eukaryotic mRNAs, plays a critical role in RNA metabolic processes such as splicing, stability, translation, and transport. Given the high energy demands of RGCs, mitochondrial dysfunction, which leads to impaired ATP production and increased ROS levels, is often central to the progression of retinal neurodegenerative disorders. However, the epigenetic mechanisms underlying m6A modification and their contributions to these conditions remain unclear.Patient-specific iPSCs were generated from individuals with Leber's hereditary optic neuropathy (LHON) and differentiated into retinal ganglion cells (RGCs) within retinal organoids. To analyze m6A methylation, we employed quantitative PCR and focused on differential expression of key m6A-modifying enzymes.METHODSPatient-specific iPSCs were generated from individuals with Leber's hereditary optic neuropathy (LHON) and differentiated into retinal ganglion cells (RGCs) within retinal organoids. To analyze m6A methylation, we employed quantitative PCR and focused on differential expression of key m6A-modifying enzymes.iPSC-derived retinal organoids are adaptable for studying and investigating the epigenetic mechanisms of retinal neurodegenerative diseases. Our data demonstrated the profiling of global m6A-related gene expression levels in LHON patient-derived iPSC-RGCs compared with controls, highlighting specific disruptions in m6A modification pathways.RESULTSiPSC-derived retinal organoids are adaptable for studying and investigating the epigenetic mechanisms of retinal neurodegenerative diseases. Our data demonstrated the profiling of global m6A-related gene expression levels in LHON patient-derived iPSC-RGCs compared with controls, highlighting specific disruptions in m6A modification pathways.These findings suggest that differential m6A modifications may play pivotal roles in the pathogenesis of retinal neurodegenerative diseases and affect the progression of the disease in affected individuals.CONCLUSIONThese findings suggest that differential m6A modifications may play pivotal roles in the pathogenesis of retinal neurodegenerative diseases and affect the progression of the disease in affected individuals.